ANALISIS KELAYAKAN USAHA DAN RANTAI NILAI SAYURAN DI DESA LAWOILA KABUPATEN KONAWE SELATAN (Feasibility Analysis Of Vegetable Business And Value Chain In Lawoila Village, South Konawe Regency) - HARIANTI, HARIANTI; HASRIATI, HASRIATI; SYAHADAT, MUHAMMAD; TAO, HAERUDIN (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2026)
Vegetable agribusiness is important for making ensuring there is enough food and for helping farmers earn more money. But how well it works relies a lot on how simple it is to conduct business and how effectively the value chain works. This study aims to assess the economic feasibility and value chain framework of vegetable agribusiness in Lawoila Village, South Konawe Regency. The study used a quantitative descriptive technique, using primary data collected from interviews with farmers, middlemen, and dealers. The research looked at the expenses and revenues, the R/C Ratio, the B/C Ratio, the profitability, and the marketing margins. Each planting season, it cost an average of Rp3,287,333 to cultivate vegetables, and the total income was Rp5,775,000. The net income was Rp2,487,667, which indicates this. The R/C Ratio is 1.76 and the B/C Ratio is 0.76, thus you can produce vegetables and earn money doing it. Customers paid Rp7,000 for each bundle, while farmers paid Rp3,000 for each bundle. This meant that the overall marketing margin for each product was Rp4,000. The middlemen and merchants get most of the value that is produced. This suggests that the benefits throughout the value chain are not yet evenly divided out.